2014
DOI: 10.1186/s12974-014-0140-4
|View full text |Cite
|
Sign up to set email alerts
|

Lithium ameliorates lipopolysaccharide-induced microglial activation via inhibition of toll-like receptor 4 expression by activating the PI3K/Akt/FoxO1 pathway

Abstract: BackgroundLithium, an effective mood stabilizer for the treatment of bipolar disorders, has been recently suggested to have a role in neuroprotection during neurodegenerative diseases. The pathogenesis of neurological disorders often involves the activation of microglia and associated inflammatory processes. Thus, in this study, we aimed to understand the role of lithium in microglial activation and to elucidate the underlying mechanism(s).MethodsPrimary microglial cells were pretreated with lithium and stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 39 publications
2
71
0
Order By: Relevance
“…It has been shown that inhibiting TLR4 expression can suppress LPS-stimulated production of IL-β and TNF-α in the BV-2 microglia cell line [22]. Our previous study showed that pre-treatment with lithium inhibits LPS-induced TLR4 expression and microglial activation through the PI3K/Akt/FoxO1 signaling pathway, which is in accordance with the results in this study [15]. We found that co-incubation with glucose and LPS increased the expression of TLR4 (Fig.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…It has been shown that inhibiting TLR4 expression can suppress LPS-stimulated production of IL-β and TNF-α in the BV-2 microglia cell line [22]. Our previous study showed that pre-treatment with lithium inhibits LPS-induced TLR4 expression and microglial activation through the PI3K/Akt/FoxO1 signaling pathway, which is in accordance with the results in this study [15]. We found that co-incubation with glucose and LPS increased the expression of TLR4 (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…It is known that the JAK2/STAT3 pathway plays a role in regulating the expression of TLR4 in macrophages [16]. Our previous study demonstrated that TLR4 can regulate microglia activation and inflammatory response [15]. Thus, we next tested the hypothesis that high glucose could accelerate LPS-induced microglia inflammation via the JAK2/STAT3 pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, blockage of PI3K by its inhibitor LY294002 has been found to suppress tetrachlorodibenzo-pdioxin (TCDD) -enhanced proliferation of HAPI microglial cells (Xu et al, 2014). FoxO1, a member of the forkhead transcription factor family (FoxO), has been found to be a modulator in microglial activation induced by PI3K/Akt (Dong et al, 2014), and further, Akt activation has been found to precede NF-κB activation in inflammatory responses of activated microglia, which shows that Akt was upstream of NF-κB (Saponaro et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that inhibiting TLR4 expression can suppress LPS-stimulated production of IL-β and TNF-α in the BV-2 microglia cell line [35]. Our previous studies have confirmed the role of TLR4 in microglia activation clearly [26,36], but the precise effect of TLR4 on astrocytes activation remains to be elucidated. Recent data has showed that after TLR4 activation, astrocytes may cause alterations on the blood brain barrier (BBB), promote inflammation, and modulate immune responses [14].…”
Section: The Effect Of Lithium On Tlr4 In Astrocytesmentioning
confidence: 49%